PENGARUH PENGGUNAAN ALAT KONTRASEPSI DAN MIGRASI PENDUDUK TERHADAP PERTUMBUHAN PENDUDUK DI PROVINSI SUMATERA UTARA - Rizky Andrian; Zulkifli Siregar; M. Sahnan (JEKKP (Jurnal Ekonomi, Keuangan dan Kebijakan Publik), 2021)
In this study, population growth in North Sumatra Province has increased and decreased every year. This is due to the factors of the use of contraceptives and migration which have increased and decreased every year. The formulation of the problem in this study is how the Effect of Contraceptive Use and Population Migration on Population Growth in North Sumatra Province and is limited only to the use of contraceptives, population migration and population growth in North Sumatra Province in 2016-2020. The purpose of this study was to determine the effect of the use of contraceptives and population migration on population growth in the province of North Sumatra. The hypothesis in this study is that the use of contraceptives and population migration has an effect on population growth in the province of North Sumatra. The population of this study is the report on the Use of Contraceptive Devices, Population Migration and Population Growth in 2016-2020. The sample used is taken from the entire population, namely as many as 33 regencies/cities in North Sumatra Province and multiplied by 5 years in order to obtain 165 research samples. The analysis technique used is multiple regression analysis, t test and F test were conducted to test the effect partially and simultaneously between the independent variable and the dependent variable with the assumption that other variables are considered constant. Based on the results of the partial test, it is known that the variables of Contraceptive Device Use (X1) and Population Migration (X2) have an influence on Population Growth (Y). Based on the results of the simultaneous test, it was found that the Use of Contraceptive Devices (X1) and Population Migration (X2) had a simultaneous (simultaneous) effect on the Population Growth variable (Y). Based on the results of the coefficient of determination test, the R square value is 0.544. This means that the effect of the independent variable on the dependent variable is 54.4%, while the remaining 0.456 or 45.6% is influenced by other variables not included in this study.